(untitled) (Revista Contexto & Educação, 2022)
This article presents a historical overview of the violent process that the peoples of Brazil and the African peoples suffered in Brazil at the time of colonization. Therefore, the article takes a historical tour of the history of Brazil, starting in the 1500, going through the enslavement of indigenous peoples and moving through the enslavement of African peoples subjected to slavery by the colonial elites of the time. The purpose of this article is to provide a historical overview of the violent process of enslavement of the indigenous population and the black population in Brazil. To carry out this work, we chose the literature review as a methodological resource. In view of what was presented in the course of this work, we can consider that since the beginning of the colonization of Brazil, minority populations such as indigenous and enslaved Africans have been subjected to different types of violence, which still reverberate today.